Strategy of the Sidoarjo District Transportation Office in Improving Service Quality Through the Drive-Thru Driver's License Test - Muhammad Akbar Putra Handoyo; Bayu Priambodo (Publik : (Jurnal Ilmu Administrasi), 2025)
This study was motivated by the declining number of drive-thru service users at UPT PKB Sidoarjo Regency in 2024. The existence of long queues due to the limited number of service counters, the absence of a special lane for drive-thru, inadequate parking, and brokering practices have hampered the smooth process of drive-thru KIR test services. This study aims to analyze strategies to improve the quality of motor vehicle feasibility test services through the drive thru system at the Sidoarjo Regency Motor Vehicle Testing Technical Implementation Unit (UPT PKB). This research uses a qualitative method with a descriptive approach, and uses the theory of service quality improvement strategies, which includes eight dimensions. The dimension of identifying determinants of service quality is considered not to be running optimally; managing customer expectations is also not optimal; managing evidence of service quality is not running optimally. Meanwhile, educating customers about services is considered to be running optimally. Developing a culture of quality is also optimal. Creating service automation (automating quality) is considered to be running optimally. Following up on services is also considered optimal. However, developing service information systems has not been optimal. It can be seen that the strategy to improve service quality is quite optimal, with 4 dimensions considered optimal and 4 other dimensions not running optimally.